Comparative evaluation of marginal fit and axial wall adaptability of copings fabricated by metal laser sintering and lost-wax technique: An in vitro study - Bhushan Satish Gaikwad; Girish Nazirkar; Rajani Dable; Shailendra Singh (Wolters Kluwer Medknow Publications, 2018)
Purpose: The present study aims to compare and evaluate the marginal fit and axial wall adaptability of Co-Cr copings fabricated by metal laser sintering (MLS) and lost-wax (LW) techniques using a stereomicroscope. Materials and Methods: A stainless steel master die assembly was fabricated simulating a prepared crown; 40 replicas of master die were fabricated in gypsum type IV and randomly divided in two equal groups. Group A coping was fabrication by LW technique and the Group B coping fabrication by MLS technique. The copings were seated on their respective gypsum dies and marginal fit was measured using stereomicroscope and image analysis software. For evaluation of axial wall adaptability, the coping and die assembly were embedded in autopolymerizing acrylic resin and sectioned vertically. The discrepancies between the dies and copings were measured along the axial wall on each halves. The data were subjected to statistical analysis using unpaired t-test. Results: The mean values of marginal fit for copings in Group B (MLS) were lower (24.6 μm) than the copings in Group A (LW) (39.53 μm), and the difference was statistically significant (P < 0.05). The mean axial wall discrepancy value was lower for Group B (31.03 μm) as compared with Group A (54.49 μm) and the difference was statistically significant (P < 0.05). Conclusions: The copings fabricated by MLS technique had better marginal fit and axial wall adaptability in comparison with copings fabricated by the LW technique. However, the values of marginal fit of copings fabricated that the two techniques were within the clinically acceptable limit (<50 μm).